Immunoturbidimetric assay for in-process determination of polyclonal antibody functionality - Raaska, Iida (My University, 2024)
Polyclonal antibodies are used in diagnostic tests because of their multi-epitope binding abilities, higher sensitivity ranges than monoclonal antibodies in some assays, high avidity binding, abilities to form lattices with antigens, biophysical diversity that makes them more resistant to environment changes such as pH and temperature and cost-effectiveness. However, the use of polyclonal antibodies presents challenges such as limited specificity and variability between batches. To tackle the challenges, monitoring the functionality of polyclonal antibodies facilitates the production of more uniform batches. In this study, biolayer interferometry and immunoturbidimetric methods were developed and compared to the study, which would be more suitable for monitoring the production process. Very early in the study, it was noticed that the immunoturbidimetric alternative was more suitable for the use of Aidian and it was further developed. In the development of the method, the number of measurement points, the incubation time, the form of haemoglobin used as an analyte, and the azide possibly reacting with haemoglobin were examined. In the final method, 18 measuring points were used at equal concentration intervals, so that the titre could be determined as precisely as possible, and a pseudo-endpoint of 1000 seconds was chosen as the incubation time. In the comparison of haemoglobin forms, methaemoglobin gave 80% higher titres than the comparative oxyhaemoglobin. Based on the results, the azide did not affect the titre but increased the response signal.
Keywords: Polyclonal antibody, biolayer interferometry, immunoturbidimetry, haemoglobin